Core Decompression as Treatment in Avascular Necrosis of the Femoral Head (Journal of Academic Research, 2025)
Core decompression is a minimally invasive surgical procedure commonly used to treat avascular necrosis (AVN) of the femoral head, a condition caused by disrupted blood supply leading to bone death and eventual joint collapse. The procedure involves drilling one or more small channels into the necrotic bone to relieve intraosseous pressure, enhance vascularization, and stimulate the formation of new bone tissue. Core decompression is most effective in the early stages of AVN (Ficat stages I and II), where joint collapse has not occurred.Clinical outcomes :suggest significant pain relief and improved function in patients with early-stage AVN. When combined with adjunct therapies, such as bone grafts, stem cells, or biologics, the success rate improves further. While it is generally considered safe,complications :such as fractures are possible. This review highlights the indications, technique, efficacy, and potential complications of core decompression for AVN of the femoral head.